2022
DOI: 10.1038/s41467-022-32085-7
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial resistance to zinc poisoning requires assembly of P-ATPase-containing membrane metal efflux platforms

Abstract: The human pathogen Mycobacterium tuberculosis requires a P1B-ATPase metal exporter, CtpC (Rv3270), for resistance to zinc poisoning. Here, we show that zinc resistance also depends on a chaperone-like protein, PacL1 (Rv3269). PacL1 contains a transmembrane domain, a cytoplasmic region with glutamine/alanine repeats and a C-terminal metal-binding motif (MBM). PacL1 binds Zn2+, but the MBM is required only at high zinc concentrations. PacL1 co-localizes with CtpC in dynamic foci in the mycobacterial plasma membr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…PacL1 is composed of a transmembrane (TM) N-terminal segment, a cytoplasmic region harboring Glu/ Ala (EA) repeats and exhibiting the conserved DUF1490 domain, and a C-terminal intrinsically disordered region (IDR) with a zinc metal-binding motif. We showed that PacL1 is essential for CtpCdependent zinc tolerance in vivo (Boudehen et al, 2022) Altogether, these observations suggest the existence of clusters of metal efflux pumps, which we named metal efflux platforms, organized in the membrane by the PacL proteins (Boudehen et al, 2022).…”
Section: Controlling the Stability Of A Membrane Transporter Through ...mentioning
confidence: 76%
See 4 more Smart Citations
“…PacL1 is composed of a transmembrane (TM) N-terminal segment, a cytoplasmic region harboring Glu/ Ala (EA) repeats and exhibiting the conserved DUF1490 domain, and a C-terminal intrinsically disordered region (IDR) with a zinc metal-binding motif. We showed that PacL1 is essential for CtpCdependent zinc tolerance in vivo (Boudehen et al, 2022) Altogether, these observations suggest the existence of clusters of metal efflux pumps, which we named metal efflux platforms, organized in the membrane by the PacL proteins (Boudehen et al, 2022).…”
Section: Controlling the Stability Of A Membrane Transporter Through ...mentioning
confidence: 76%
“…Some may rely on physical properties such as phase separation (Heinkel et al, 2019), membrane curvature (Saaki et al, 2018), or preferential interactions with specific lipids, such as those forming lipid domains (Alvarez & Georgellis, 2019; Barák & Muchová, 2013) or the carotenoids enriched in FMM (García‐Fernández et al, 2017; López & Kolter, 2010). Some nanodomains can form through protein–protein interactions with specific scaffold proteins such as flotillins or the PacL proteins (Boudehen et al, 2022; García‐Fernández et al, 2017). The emergence of this new field will greatly enhance our understanding of membrane biology and its integration in bacterial physiology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations